2015
DOI: 10.2141/jpsa.0150066
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Tenderization of Duck Breast Meat by Adenosine 5′-Monophosphate (AMP) using Response Surface Methodology

Abstract: This study aimed to characterize and optimize the tenderization condition of duck breast meat by adenosine 5′ -monophosphate (AMP), with the aid of response surface methodology (RSM). The results showed that the optimal conditions for the tenderization of duck breast meat were at the NaCl concentration of 3.99 g/100 g, AMP concentration of 13.83 mmol/L, temperature of 15.32℃, and marinating time of 8 h. Compared with control duck breast meat, AMP combined with NaCl treatment demonstrated significant effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…The MFI values of AMP were higher than those of Control and DW. Wang et al [18] reported that AMP marination exhibited a significant increased MFI over the untreated duck breast, which was consistent with our results. The reason UAMP has a remarkable ability to increase MFI might be due to the ultrasound causing mechanical and acoustic cavitation, and turbulence.…”
Section: Resultssupporting
confidence: 93%
“…The MFI values of AMP were higher than those of Control and DW. Wang et al [18] reported that AMP marination exhibited a significant increased MFI over the untreated duck breast, which was consistent with our results. The reason UAMP has a remarkable ability to increase MFI might be due to the ultrasound causing mechanical and acoustic cavitation, and turbulence.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, duck meat and its products have gained increased consumer interest since it is recommended to reduce the intake of red meat, which has been related to cardiovascular disease (Adzitey et al 2012;Witak, 2008;Zou et al 2017b). The consumption of duck meat and its products has increased about twofold in China between 2000 and 2011 (Wang et al 2013;Wang et al 2016;Wang et al 2014). Therefore, the development of new products, preferentially containing antioxidant peptides, is necessary.…”
Section: Introductionmentioning
confidence: 99%